62. Detectors comparison for absorbed dose and output factors determination in high dose per pulse electron beams produced by a mobile linac for Intra Operative Radiation Therapy (IORT). (December 2018) - Andreoli, S.; Pimpinella, M.; Angelis, C. De; Menegotti, L.; Silvi, L.; Monaca, S. Della
Abstract : Purpose: Evaluating the level of agreement of measurements by different types of ionization chambers and solid state detectors in IORT electron beams with high dose per pulse. Methods: Two electron beams (R50 2.59 and 3.05 cm) by a Novac7 Hitesys linac were used. Absorbed dose to water (Dw) and output factors (OF) were determined for the reference applicator of diameter 10 cm and the clinical applicators of diameter from 4 to 7 cm. The dose per pulse ranged between 29 and 77 mGy. Six types of plane parallel ionization chambers (PTW Markus, Advanced Markus and Roos; IBA PPC05, PPC40 and NACP02) were utilized. OF measurements were also made using a PTW microDiamond type 60019 and silicon diodes PTW type 60017 and IBA-EFG-3D. The IAEA TRS-398 dosimetry protocol was applied except for the saturation corrections applied to the ionization chambers that were determined according to[1] . Results: The PPC05 and the Advanced Markus chambers exhibited the lowest ion recombination effects, being the corrections to be applied lower than 0.5% and 1.5%, respectively. Corrections larger than 15% were obtained for the Roos, the and PPC40 and the NACP02. Agreement among ionization chamber OF values was generally better than 1.5% except for the largest chambers in the smallest beams, where beam non uniformity likely caused dose underestimation, and for some discrepancies relevant to the Markus and the NACP02 chambers. OF values obtained using the solid state detectors typically agreed within 1.5%, while differences from PPC05 and Advanced Markus OFs were within 2%. Dw measurements by means of different ionization chambers agree to each other within the stated uncertainties (2.5%, 1SD). Conclusions: Results of this work show that, at the high dose per pulse of NOVAC7 beams, dosimetry based on ionimetric measurements is feasible, if ion recombination effects are properly taken into account, and the studied solid state detectors are suitable for relative dosimetry.